(untitled) (ENTHYMEMA, 2013)
The essay explains Giovanni Verga’s Malavoglia according to the narrative theory of Franz Karl Stanzel, arguing that the novel provides an example of the figural narrative situation. The figuralization (or reflectorization) of Malavoglia is achieved mainly by the so-called (the definition is Ann Banfield’s ) non-reflective consciousness, that is, by the perceptive interplay of characters, independent of the intervention of an actual narrator. Such a methodological point of view implies a revision of some typological features of modernist novel, which has been too often interpreted only through texts of the “northern” Flaubert-James-Joyce-Woolf line.